Observing Optional Number in DDC Edition 23 - Mohamad, Rotmianto (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2015)
Dewey Decimal Classification is a most popular classification system in the world because of its completeness and most up-to-date. There are many optional number in this classification system, although it rarely to be discussed even it is important to known well about that optional number, especially for a librarian as classifier. This paper is a literature study about Dewey Decimal Classification Edition 23, to describe about optional numbers, particularly the number in relationship with Indonesiaâs subject and discipline. This paper is to avoid misunderstanding in interpreted about optional number among librarians, especially for who that does not understand well about optional numbers. Â